Media Literacy Education at the University Level: A Case study of the South East European University (SEEU) - Demush Bajrami; Edlira PALLOSHI DISHA; Albulena Halili; Shemsedin Ibrahimi (Institute of Communication Studies, 2022)
Media literacy education is the key to creating citizens resilient to fake news and disinformation, especially in countries vulnerable to foreign influence, such as North Macedonia. The impact of disinformation in the country is higher compared to developed democratic countries. Referring to the highly polarized society, with a weak education system, citizens' low trust in institutions and media as well as average or low level of investigative journalism, it is high time that media literacy should be institutionalized in North Macedonia, particularly at the university level. This study argues that the introduction of media literacy programs and/or courses at the university level is indispensable. The sui-generis nature and the unique experience of the South East European University in higher education in North Macedonia, as well as its reputation as a Western model of higher education, makes it clearly suitable to be a leader in the institutionalization of media literacy education. Furthermore, it aims to justify the need of including media literacy courses at each faculty at the South East European University, while creating new curricula and/or study programs at the Department of Communication Sciences and Faculty of Contemporary Social Sciences. Moreover, the recently established Media Literacy and Disinformation Research Cluster which functions at the Max van der Stoel Research Institute will complement the proposed reform in the curricula of these faculties. The results from the theoretical research and those from empirical research through the online survey with undergraduate and master students further argue that media literacy education is an inevitable need in the digital era that educates university students to critically approach information online, while contributing to creating a resilient society as an ultimate goal.